Pola Pasien Anemia yang dirawat Inap di RS UKRIDA Tahun 2021-2023 - Allotodang, Thiessa Gabriel; Pandapotan, Roy Akur; Suhayanly, Nella (Universitas Kristen Krida Wacana, 2025)
Anemia is when hemoglobin levels fall below normal levels and are unable to provide oxygen to body tissues. Symptoms may include lethargy, fatigue, weakness, ringing in the ears, cold feet, shortness of breath, eye strain, and dyspepsia. Several processes, including decreased red blood cell production, increased red blood cell destruction, and blood loss, can cause anemia. The number of anemia cases in Indonesia ranks fifth in Southeast Asia. Three types of anemia are normocytic normochrome, microcytic hypochrome, and macrocytic. This study aims to determine the pattern of anemia patients hospitalized at UKRIDA Hospital in 2021-2023. This research is a descriptive study with a cross-sectional design. The results showed that anemia is more common in the 18-60 age group (60%), but quite a lot also occurs in geriatrics due to nutritional deficiencies and chronic diseases. Anemia was more common in women (80%). The majority of patients (93.8%) had comorbid diseases, with the most common conditions including type 2 diabetes mellitus, hypertension and chronic kidney disease. Only 13.8% of patients underwent surgery while 61.5% of patients received blood transfusions. The most common type of anemia experienced was normocytic normochrome anemia.